2019
DOI: 10.1111/ijn.12768
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about medicines as mediators in medication adherence in type 2 diabetes

Abstract: Aims This study analysed whether beliefs about medicines mediated the relationship between illness representations and medication adherence. Background Adherence to medication is required in diabetes treatment, contributing to decreased blood glycaemic levels. The knowledge and perception of patients about diabetes as well as the beliefs about medicines are considered to be key factors for medication adherence. Design The study used a cross‐sectional design that included 387 patients recently diagnosed with ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…50 In a study by Graça Pereira et al on a group of 382 patients with type 2 diabetes, greater concerns about the diabetes, weaker general beliefs about medicines, and stronger needs about medicines were associated with higher levels of adherence to treatment. 49 In turn, Yoel et al confirmed the impact of adverse effects of the prescribed medication on adherence. 50 Patients with poorer adherence reported that the adverse effects from the prescribed medication were worse than their disease symptoms (65 vs 47%), which represented the main reason for discontinuation of treatment in nearly half of the patients studied.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…50 In a study by Graça Pereira et al on a group of 382 patients with type 2 diabetes, greater concerns about the diabetes, weaker general beliefs about medicines, and stronger needs about medicines were associated with higher levels of adherence to treatment. 49 In turn, Yoel et al confirmed the impact of adverse effects of the prescribed medication on adherence. 50 Patients with poorer adherence reported that the adverse effects from the prescribed medication were worse than their disease symptoms (65 vs 47%), which represented the main reason for discontinuation of treatment in nearly half of the patients studied.…”
Section: Resultsmentioning
confidence: 97%
“… 17–21 , 26–31 , 39–42 , 45–48 A further 16 study were identified through reference searches. 22–25 , 32–38 , 43 , 44 , 49–52 No studies were found on the association of frailty syndrome and addiction with adherence of patients with type 2 diabetes.…”
Section: Methodsmentioning
confidence: 99%
“…Two of these evaluated general beliefs on medication adherence were assessed as one factor without measuring harm or overuse beliefs. In both of these studies, a negative association with medication adherence was reported [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…1 Also, if a patient believes their condition will adversely affect their life to a great extent, they will be adherent. 17 Thus, a belief in the necessity of medication in treating or curing a condition can be balanced or offset by one' s concerns about the medication' s potential adverse reactions or the impact of medications. In other words, patients constantly engage in a riskbenefit analysis of their medications.…”
Section: Highlighted Five Factors Thatmentioning
confidence: 99%